2021
DOI: 10.3390/met11111868
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructure and Properties of the Nb-23Ti-5Si-5Al-5Hf-5V-2Cr-2Sn (at.%) Silicide-Based Alloy—RM(Nb)IC

Abstract: The microstructure, isothermal oxidation, and hardness of the Nb-23Ti-5Si-5Al-5Hf-5V-2Cr-2Sn alloy and the hardness and Young’s moduli of elasticity of its Nbss and Nb5Si3 were studied. The alloy was selected using the niobium intermetallic composite elaboration (NICE) alloy design methodology. There was macrosegregation of Ti and Si in the cast alloy. The Nbss, αNb5Si3, γNb5Si3, and HfO2 phases were present in the as-cast or heat-treated alloy plus TiN in the near-the-surface areas of the latter. The vol.% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 53 publications
1
48
1
Order By: Relevance
“…Microstructure and properties of RM(Nb)ICs containing these elements have been studied by different groups [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. With the exception of one systematic study on the effect of the concentration of Sn (2 to 8 at.%) on the microstructure of as-cast and heat-treated (1200 • C/120 h) MASCbased Nb-25Ti-16Si-8Hf-2Al-2Cr-xSn alloys and their oxidation [16], all other studies and patents have been of Sn-free alloys (e.g., [17][18][19][20]), Hf-free alloys (e.g., [21][22][23]), Al-, Cr-, and Sn-free alloys (e.g., [24,25]), Ti-free alloys [26], or alloys where the elements Al, Cr, Hf, Si, Sn and Ti were in synergy with other TMs or RMs or REs (e.g., [27][28][29][30][31]). (MASC is the RM(Nb)IC Nb-25Ti-16Si-8Hf-2Al-2Cr developed by General Electric [32].)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructure and properties of RM(Nb)ICs containing these elements have been studied by different groups [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. With the exception of one systematic study on the effect of the concentration of Sn (2 to 8 at.%) on the microstructure of as-cast and heat-treated (1200 • C/120 h) MASCbased Nb-25Ti-16Si-8Hf-2Al-2Cr-xSn alloys and their oxidation [16], all other studies and patents have been of Sn-free alloys (e.g., [17][18][19][20]), Hf-free alloys (e.g., [21][22][23]), Al-, Cr-, and Sn-free alloys (e.g., [24,25]), Ti-free alloys [26], or alloys where the elements Al, Cr, Hf, Si, Sn and Ti were in synergy with other TMs or RMs or REs (e.g., [27][28][29][30][31]). (MASC is the RM(Nb)IC Nb-25Ti-16Si-8Hf-2Al-2Cr developed by General Electric [32].)…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chemical inhomogeneity can be important vis-à-vis the contamination of RM(Nb)ICs with interstitials [20,22,23]. The contamination of the aforementioned phases with interstitials differs (for example, it is more severe for Nb ss than Nb 5 Si 3 ) and depends on their chemical composition (e.g., [20,22,23,31]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, note that with the exception of TT8, the Δχ Nbss in the other alloys is less than 0.105 ( Figure 8 c). Note that (a) above is not uncommon in RM(Nb)ICs, for example, see [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In reported RHEAs, WMoTaNb is famous for retaining high strength above 400 MPa at temperatures up to 1600 • C and has a great potential for high temperature applications; however, its compressive plastic strain at room temperature (RT) is inferior at 3%, severely limiting its processing formation performance [4]. The microstructure and performance of RHEAs can be changed dramatically by alloying other elements [5][6][7]. It is reported that alloying with V effectively improves the strength of WMoTaNb alloys to approximately 200 MPa at elevated temperatures of 600 • C-1200 • C [4].…”
Section: Introductionmentioning
confidence: 99%